Framing urban inequalities: Racist mobilization against immigrants in Athens - Kandylis, George; Kavoulakos, Karolos Iosif (The Greek Review of Social Research, 2011)
In the last few years local anti-immigration actions in the Greek capital seemed to deepen the wider racist discourse against immigrants. Collective racist actions were embedded in specific narratives about place and inequality. In this article, after a brief discussion of the socio-spatial transformations in the residential area of the Athens city-centre, we apply framing analysis in order to explore the strategic linkages between the rejection of immigrants and urban inequalities. We find that the localization of racism is framed in general visions about inequalities. Racial and social dimensions of inequalities are mixed and used in various, complex and interconnected ways. For these inequalities to be strategically used, the city space as a contested spatio-temporal entity is also involved.